Molecular identification and expression of heat shock cognate 70 (hsc70) and heat shock protein 70 (hsp70) genes in the Pacific oyster Crassostrea gigas - Boutet, Isabelle (Cell Stress Society International, 2003)
The 70-kDa heat shock protein (Hsp) family is composed of both environmentally inducible (Hsp) and constitutively expressed (Hsc) family members. We sequenced 2 genes encoding an Hsp70 and an Hsc70 in the Pacific oyster Crassostrea gigas. The Cghsc70 gene contained introns, whereas the Cghsp70 gene did not. Moreover, the corresponding amino acid sequences of the 2 genes presented all the characteristic motifs of the Hsp70 family. We also investigated the expression of Hsp70 in tissues of oysters experimentally exposed to metal. A recombinant Hsc72 was used as an antigen to produce a polyclonal antibody to quantify soluble Hsp70 by enzyme-linked immunosorbent assay in protein samples extracted from oysters. Our results showed that metals (copper and cadmium) induced a decrease in cytosolic Hsp70 level in gills and digestive gland of oysters experimentally exposed to metal. These data suggest that metals may inhibit stress protein synthesis.